EFEKTIVITAS PENGGUNAAN METODE STRUKTURAL ANALITIK SINTETIK TERHADAP KEMAMPUAN LITERASI PESERTA DIDIK KELAS II - Nur Galib; Andi Halimah; Rosdiana Rosdiana; M Fatahullah (Universitas Islam Negeri Alauddin Makassar, 2022)
This study is a pre-eksperimental design study that aims: 1) To determine the literacy ability ofstudents before using the synthetic analytical structural method in class II SDN 154 SekkangSoppeng Regency, 2) To determine the literacy ability of students after using the syntheticanalytical structural method in class II SDN 154 Sekkang Soppeng Regency and 3) To determinethe effectiveness of the use of synthetic analytical structural methods on the literacy skills of secondgrade students at SDN 154 Sekkang Soppeng Regency. Sampling was carried out using thesaturated sample technique so that the number of samples obtained was 12 students. The researchinstrument used was a literacy test sheet, namely reading. The data analysis used in this study wasdescriptive and inferential statistical analysis techniques with the help of the SPSS 20 application.Based on the results of literacy skills before and after using the synthetic analytical structuralThis study is a pre-eksperimental design study that aims: 1) To determine the literacy ability ofstudents before using the synthetic analytical structural method in class II SDN 154 SekkangSoppeng Regency, 2) To determine the literacy ability of students after using the syntheticanalytical structural method in class II SDN 154 Sekkang Soppeng Regency and 3) To determinethe effectiveness of the use of synthetic analytical structural methods on the literacy skills of secondgrade students at SDN 154 Sekkang Soppeng Regency. Sampling was carried out using thesaturated sample technique so that the number of samples obtained was 12 students. The researchinstrument used was a literacy test sheet, namely reading. The data analysis used in this study wasdescriptive and inferential statistical analysis techniques with the help of the SPSS 20 application.Based on the results of literacy skills before and after using the synthetic analytical structuralmethod there were differences, namely before using the synthetic analytical structural method withthe highest score of 60 and the lowest 40 with an average the average is 47.08, while after using thesynthetic structure analysis method the highest value is 83 and the lowest is 60 so that the averageis 73.42. This can be seen in the t-test analysis that has been carried out using a paired sample ttestwith the help of SPSS 20 which shows Thit = 14,189 with Ttable = 2,262. So it can beconcluded that the synthetic analytic structural method is effective on the literacy skills of secondgrade students at SDN 154 Sekkang Soppeng Regency.method there were differences, namely before using the synthetic analytical structural method withthe highest score of 60 and the lowest 40 with an average the average is 47.08, while after using thesynthetic structure analysis method the highest value is 83 and the lowest is 60 so that the averageis 73.42. This can be seen in the t-test analysis that has been carried out using a paired sample ttestwith the help of SPSS 20 which shows Thit = 14,189 with Ttable = 2,262. So it can beconcluded that the synthetic analytic structural method is effective on the literacy skills of secondgrade students at SDN 154 Sekkang Soppeng Regency.